Important criteria for preparation of 3D printer filaments from polymer biocomposites - Shamsuri, Ahmad Adlie (ScienceVolks, 2019)
Nowadays, there are many types of 3D printer filaments have been produced to fulfill the demand of small-scale fabrication industry. The use of polymer biocomposites as 3D printer filaments is one of the ways to reduce the depend-ence on the synthetic thermoplastics that are expensive and non-biodegradable. This is due to the utilization of natural fibers as fillers that can decrease the percentage of synthetic thermoplastics usage. Nevertheless, there are some criteria must be considered to ensure the quality of the 3D printed products fabricated from the biocomposites is good as existing filaments. This paper has briefly explained some important criteria that recently identified before preparing 3D printer filaments from polymer biocomposites.